IMPLEMENTASI SENAM NIFAS PADA PASIEN POST SECTIO CAESAREA DALAM MENURUNKAN NYERI PASCA PERSALINAN DI WILAYAH KERJA PUSKESMAS MACCINI SAWAH KOTA MAKASSAR - Limbong, Magdalena; Desi Ratnasari. S; Kasim, Erna; Hafida, Ekayanti Hafidah (Bina Generasi : Jurnal Kesehatan, 2025)
Introduction: Sectio caesarea is the main choice for medical personnel. Sectio Caesarea is a surgical procedure during childbirth that requires opening the abdominal wall or incision of the uterine abdomen so that the mother will feel pain Objective: To find out how pain is in post-cesarean section patients before and after implementation postpartum exercise Method: In this study the method used was descriptive by conducting interviews and questionnaires on 2 respondents post caesarean section patients in the Maccini Sawah Community Health Center working area with sample criteria. Inclusion criteria, namely patients willing to be respondents, post caesarean section patients 5 days and above, moderate to severe pain scale (4 - 9), primiparous type of delivery and maternal age of 17-35 years. Exclusion criteria are post caesarean section patients who are uncooperative, patients experiencing other diseases, patients who have just taken pain medication. Results: Based on the results of case studies conducted on Mrs. H1 and Mrs. H2, the client's pain was in severe pain and after postpartum exercise the client had pain. decreases with the pain scale decreasing by 1 scale for each implementation Conclusion: So it can be concluded that the implementation of postpartum exercise can reduce postpartum pain in caesarean section mothers.